Gender-Inclusive Climate Change Adaptation Policies An Empirical Analysis of Climate Swap Funding Impact Using Two-Step GMM Technique - Ahmad U.S.; Safdar. S; Anwer M.S.; Zia Ur Rehman (NUST Journal of Social Sciences and Humanities)
Climate change poses significant impact on human wellbeing, weakens economic stability and exacerbates social inequalities. Climate change adaptation policies mitigate this impact by considering the diverse gender-inclusive socio-demographic characteristics of the population. These policies ensure equitable and resilient outcomes to enhance the integration of gender-inclusive socio-demographic and climate change adaptation mechanisms. The objective of this research is to develop the dynamic nexus among climate change adaptation policies, gender-inclusive socio-demographic characteristics and climate swap funding. This study will be based on Ramsey-Cass-Koopmans macro-economic model incorporating gender inclusive socio-demographic characteristics of household. Considering the women empowerment a gender-inclusive socio demographic characteristic in climate change adaptation policies in the model. The panel dataset will be used to analyze the theoretical nexus in 46 developing economies for the period of 20 years from 2003-2022. Meanwhile, the study will also be empirically validated through innovative econometric approach Two Step System GMM. This technique is suitable as it investigates endogeneity factors besides gender inclusive socio-demographics that affect climate change adaptation policies. The expected outcomes resonate with the theory that gender-inclusive socio-demographic characteristic of household especially empowered women are crucial in climate change adaptation policies.